Proof: Do Expr At Unchanged 13
Let's prove the following theorem:
if the following are true:
- expression state at time 13 = "begin_expr"
- the expression at time 13 =
__eq__(7, 9)
then the expression at time 14 = __eq__(7, 9)
Proof:
Given
1 | expression state at time 13 = "begin_expr" |
---|---|
2 | the expression at time 13 = __eq__(7, 9) |
# | Claim | Reason |
---|---|---|
1 | the expression at time (13 + 1) = the expression at time 13 | if expression state at time 13 = "begin_expr", then the expression at time (13 + 1) = the expression at time 13 |
2 | the expression at time (13 + 1) = __eq__(7, 9) |
if the expression at time (13 + 1) = the expression at time 13 and the expression at time 13 = __eq__(7, 9) , then the expression at time (13 + 1) = __eq__(7, 9) |
3 | 13 + 1 = 14 | 13 + 1 = 14 |
4 | the expression at time (13 + 1) = the expression at time 14 | if 13 + 1 = 14, then the expression at time (13 + 1) = the expression at time 14 |
5 | the expression at time 14 = __eq__(7, 9) |
if the expression at time (13 + 1) = the expression at time 14 and the expression at time (13 + 1) = __eq__(7, 9) , then the expression at time 14 = __eq__(7, 9) |
Comments
Please log in to add comments